Islamic International Law and the right of self-defence of states - Hamid, Abdul Ghafur@Khin Maung Sein (Yijun Institute of International Law, 2009)
Islamic international law is a branch of the Shari’ah (Islamic law). Due to the classical doctrine of the notion of ‘Jihad,’ there have been misconceptions and Islam has been painted as a religion encouraging violence and war. This paper appeals for the reconsideration of the classical doctrine, which was adopted at a time when there was a state of war between Islamic and non-Islamic states. Going back to the roots and referring to the Qur’an and the Sunnah: the two primary sources of Islamic law, the paper argues that Islam prohibits aggressive war and that the essence of ‘jihad’ is‘self-defense.’ After elaborating the essential conditions of the right of self-defense, the paper concludes that Islamic international law can contribute much to the present world order by providing moral and ethical values that modern international law is lacking.